ASTHMA AND VIRAL INFECTIONS IN CHILDREN - D. Sh. Macharadze ("Paediatrician" Publishers LLC, 2014)
Viruses are the most common pathogens of acute respiratory diseases - most often causing mild symptoms of common cold: cough, runny nose, temperature increases. At the same time, 1/3 of children have the following symptoms of lower respiratory tract disorders: shortness of breath, wheezing, coughing, respiratory failure. Virus-induced wheezing are risk factors for development of asthma in childhood. Recent clinical and scientific data suggest: the more difficult are viral respiratory infections in young children, the higher their risk of asthma later on. Another feature is that children with allergic diseases are much more likely to have viral respiratory infections(and with longer clinical course), compared with children without atopy. The use of ibuprofen is safe for children over 3 months, including suffering from bronchial asthma.